PKMBP PENDAMPINGAN PERANCANGAN DESAIN LOGO DAN MEREK USAHA WISATA SAWAH DESA MATANG ARA JAWA SEBAGAI DAYA SAING MENUJU TOURISM 4.0 - Muhammad Fuad; Rini Mastuti; Fairus Fairus (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Desa Matang Ara Jawa is one of the coastal areas that is currently trying to build rice field tourism as its BUMK business unit. It was identified that efforts to develop the competitiveness of the business unit towards the Tourism 4.0 era experienced a major obstacle, namely the absence of a business logo and brand design. Therefore, the focus of this activity is to offer assistance solutions in designing the logo and brand design of the rice field tourism business owned by BUMK Matang Ara Jawa. The service method uses an active participatory approach that positions Partners as the main actors in every stage, starting from material planning and activity schedules, preparing activity tools and materials, through implementing supervision and evaluation of the performance of activities. The result obtained is a logo or brand design of a rice field tourism business in Desa Matang Ara Jawa which has obtained an intellectual property rights (IPR) certificate.